Evaluasi Penggunaan Sistem Akuntansi Pengeluaran Kas Pada Usaha Mikro Kecil dan Menengah Mealsmound.Id Kabupaten Pati - Syah, Alif Arfian (Indonesian Accounting Research Journal, 2024)
Mealsmound.Id is one of the UMKM in Pati District, Pati Regency. Mealsmound.Id UMKM operates in the trading sector which sells a variety of contemporary food desserts. The income earned by these UMKM every month reaches around 30 million. However, this business does not yet have a good accounting system, so its financial reporting is not well structured and appears to be less effective and efficient. This research uses a case study method with a qualitative approach. This research was conducted at the Mealsmound.Id shop located in Pati District, Pati Regency. This research was conducted between May and August 2024. The results of this research state that Mealsmound.Id UMKM have not implemented a standard accounting system. UMKM Mealsmound.Id does not record frequent transactions in detail, UMKM Mealsmound.Id only records sales transactions. The process of establishing a new system at UMKM Mealsmound.Id consists of: (1) Cash In Form (2) Cash Out Form (3) Profit and Loss Report. The implementation that has been carried out is based on data obtained in June 2024, resulting in total revenue for 1 June to 25 June 2024 of IDR 13,228,500 with a cost of goods sold of IDR 32,203,500 and total costs or cash out of IDR 18,975,000.